Multi-objective shape optimization of a heat exchanger tube fitted with compound inserts. (5th May 2017) - Chamoli, Sunil; Yu, Peng; Yu, Shimin
Graphical abstract: Highlights: MOO in circular tubes with compound inserts is investigated. Lower values of PR and TR produced increased heat transfer and pressure drop. Maximum relative error of prediction by RSM is 10.28% for Nu Nu s and 5.84% for f f s . The Pareto front A exhibit maximum and F shows minimum TEF. The Pareto front comprises important thermal design principles. Abstract: This paper reports a multi-objective optimization of a heat exchanger tube fitted with compound insert geometries to obtain a maximum convective heat transfer rate and minimum pressure loss. A series of experimental runs has been constructed using response surface methodology (RSM) to study the effect of geometrical and flow parameters on heat transfer and friction characteristics along with parameter optimization. The study involves the dimensionless parameters: Reynolds number ( Re ), pitch ratio ( PR ), twist ratio ( TR ), and twisted tape number ( N ). The characteristic numbers involving heat transfer characteristics (Nusselt number ratio, Nu / Nu s ) and friction characteristics (friction factor ratio, f / f s ) calculated from experimental data are served as the response variables for RSM. The objective functions for Nu / Nu s and f / f s are constructed using RSM and utilized in multi-objective genetic algorithm to obtain the Pareto-optimal fronts. The results show that the decrease in the PR, TR and increase in N, Re are measured in the augmentation of both the objective functions. It is concluded that the acquired Pareto optimal configurations provide principal understanding into the design parameters and allow autonomy of selection among the optimal solutions. A thermal enhancement factor is used to study the thermal-hydraulic performance of the Pareto optimal solutions.